2012
DOI: 10.1152/physrev.00048.2011
|View full text |Cite
|
Sign up to set email alerts
|

The Proprioceptive Senses: Their Roles in Signaling Body Shape, Body Position and Movement, and Muscle Force

Abstract: This is a review of the proprioceptive senses generated as a result of our own actions. They include the senses of position and movement of our limbs and trunk, the sense of effort, the sense of force, and the sense of heaviness. Receptors involved in proprioception are located in skin, muscles, and joints. Information about limb position and movement is not generated by individual receptors, but by populations of afferents. Afferent signals generated during a movement are processed to code for endpoint positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
1,342
1
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,559 publications
(1,380 citation statements)
references
References 399 publications
(458 reference statements)
18
1,342
1
19
Order By: Relevance
“…Specifically, several other investigators have reported an age-related decline in motion (Kokmen et al 1978;Wright et al 2011) and position sense of the upper limbs (Adamo et al 2007;Adamo et al 2009;Herter et al 2014). These deteriorations may partially be caused by physiological changes in the structure and function of muscle spindles throughout late adulthood (Herter et al 2014;Kalisch et al 2012;Proske and Gandevia 2012). Besides their gradual decline in number, aged muscle spindles generally show an increased capsular thickness, decreased diameter size, and lower sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, several other investigators have reported an age-related decline in motion (Kokmen et al 1978;Wright et al 2011) and position sense of the upper limbs (Adamo et al 2007;Adamo et al 2009;Herter et al 2014). These deteriorations may partially be caused by physiological changes in the structure and function of muscle spindles throughout late adulthood (Herter et al 2014;Kalisch et al 2012;Proske and Gandevia 2012). Besides their gradual decline in number, aged muscle spindles generally show an increased capsular thickness, decreased diameter size, and lower sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…4). Physical activity has been suggested to partially compensate for the abovementioned age-related declines in muscle functioning by entailing muscle fiber hypertrophy in older adults (Proske and Gandevia 2012). Thus, active older adults may delay their natural decline in proprioception by enhancing the signaling capacity of muscle spindles and joint movement receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it is currently thought that the principle sensory input for postural sway is proprioception [78]. The important proprioception sensors for balance are [78]: 1) muscle spindles which are arranged in parallel with muscle fibers, 2) Golgi tendon organs which are arranged in series with muscle fibers, and 3) cutaneous mechanoreceptors [32,43].…”
Section: Human Postural Swaymentioning
confidence: 99%
“…Peripheral nerve injury is thus processed in the cerebellum as a multisensory perception 56, 57. Chronic nociceptive stimuli inhibit motor output through feedback from higher processing centres in the brain 58. Direct nociceptive input to the cerebellum is also likely to play an important role 33, 34.…”
Section: Discussionmentioning
confidence: 99%